Synthesis and Characterization of Iron(II), Cobalt(II), Nickel(II), Copper(II), and Zinc(II) Complexes Using Diphenylmethyl Xanthate Ligand - Al-Fahdawi, Aeed S.; Alsalihi, Eman I. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
Potassium Diphenylmethyl Xanthate and its monomeric complexes were synthesized at room temperature under inert gas and stirring condition. The ligand and its complexes of the general formula [M(L)2] (where M= FeII, CoII, NiII , CuII, ZnII and CdII) were characterized by spectroscopic methods (IR, UV-Vis, 1H-, 13C-, DEPT-, HQMC- and COSY-NMR), elemental analysis, metal content, magnetic susceptibility measurement and molar conductance. These studies revealed the formation of four coordinate complexes.